The beauty of asymmetry: asymmetric divisions and self-renewal in the haematopoietic system - Ho, Anthony Dick; Wagner, Wolfgang (Current opinion in hematology, 2007)
Purpose of review - The hallmark of stem cells is their dual abilities to self-renew and to differentiate into multiple lineages. To fulfill these functions they must undergo asymmetric division. A central question in developmental biology is how can a single cell divide to produce two progeny cells that adopt different fates? We provided evidence of the significance of asymmetric division in human haematopoietic stem cells. - Recent findings - By monitoring the symmetry of divisions of haematopoietic stem cells and following their subsequent developmental potentials at the single cell level, we established a relationship between divisional kinetics and self-renewal capacity. Direct cell-cell contact with cellular determinants in the niche has been shown to play an essential role in maintaining stemness. The creation of in-vitro models for the niche, such as human mesenchymal stromal cells, has provided a controlled laboratory environment in which the relative significance of chemokines and adhesion molecules can be studied. - Summary - Identification of the molecular interactions between stem cells and their niche has led to an understanding of the mechanisms that control the self-renewal of stem cells. Ultimately, molecular signals triggered by adhesion and junction complexes are responsible for the adoption of specific cell fate.
Gesehen am 26.10.2021